An Analysis of Social Cost in School Level Education of Nepal - Paudel, Mina Raj (JMC Research Journal, 2018)
Social costs in education plays decisive role for education development and economic growth of a nation. In this context, this article tries to analyze the size, trend and growth rate of social cost in the education sector of Nepal by disaggregating it into total social cost, recurrent social cost, capital social cost, unit cost and marginal cost in community based school education of Nepal. The study is based on the secondary data obtained from official documents of Nepal’s Government such as flash report, budget speech, red book and so on. The time series data from 2011 AD to 2015 AD were collected for the analysis by using convenience non-random sampling method. The overall finding of the study shows that the share of the annual average social cost in education is 15.84 percent of the total cost of the government of Nepal. In other words, the government has allocated annual average Rs 68930697.6 thousands as social cost in educational sector during the study years. The average annual growth rate of this cost is 5.15 percent. The study also indicates that annual average total social cost is Rs 68930697.6 thousands, recurrent social cost is Rs 5,71,63,418.79 thousands and capital social cost is Rs 1,17,67,278.81 thousands in Nepal. Similarly, annual average total social cost is estimated to be Rs 3,33,35,928.80 thousands. The total social unit cost per teacher and total social unit cost per student are Rs 196.39 thousands and 5.51 thousands respectively. The annual average marginal social cost per teacher and marginal social cost per student are Rs 1308.08 thousands and -202.96 thousands respectively. The negative sign indicates that student enrolment has decreased over the study period. The findings of the study conclude that there is no any predictable relationship among student enrolment, teaching and non-teaching staffs and social cost of education in case of Nepal. However, UNESCO (1999) had analyzed public investment on education of 16 countries and it found that their average investment on education was 19.2 percent of GDP. Therefore, Nepal government should increase in educational investment from its current status of 15.80 percent to at least more than it in the coming years to develop educational sector of Nepal.